2015
DOI: 10.1016/j.diagmicrobio.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Is procalcitonin increased in cases of invasive amoebiasis? A retrospective, observational study

Abstract: Procalcitonin (PCT) levels are commonly used for diagnostic guidance in routine bacterial infections. By contrast, little data are currently available regarding PCT in parasitic diseases, and its role in cases of invasive amoebiasis has not yet been described. For this purpose, 35 adult patients with a proven diagnosis of invasive or digestive amoebiasis were included in a 4-year study period. Serum PCT was retrospectively assessed. Results were analysed with regard to the usual inflammatory biomarkers, like C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…A low serum albumin (< 2 g/dL) is found in almost all patients; however, an exceedingly low value is a poor prognostic marker[ 34 ]. Inflammatory biomarkers, such as C-reactive protein and procalcitonin have been found to be nonspecifically raised in most patients with ALA[ 34 , 59 , 61 ].…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…A low serum albumin (< 2 g/dL) is found in almost all patients; however, an exceedingly low value is a poor prognostic marker[ 34 ]. Inflammatory biomarkers, such as C-reactive protein and procalcitonin have been found to be nonspecifically raised in most patients with ALA[ 34 , 59 , 61 ].…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…Notably, PCT and CRP levels are elevated mainly in bacterial and in some viral infections. Although they are not used in the diagnosis of parasitic infections, it was reported that PCT or CRP levels were high, especially in invasive parasitic infections involving the liver [16][17][18][19][20][21] . It was suspected that PCT and CRP levels would increase in the pathogenesis of fascioliasis, which mainly involves the liver and biliary tract.…”
Section: Introductionmentioning
confidence: 99%
“…That procalcitonin is the response of the human body to a bacterial infection was first discovered by Dandona et al in 1990 [10]. A high level of PCT in the blood indicates not only severe bacterial infection and sepsis [11,12,13,14], but also postoperative complications [15,16,17,18]. To date, there are very few studies on the role of PCT in early detection of surgical site infections after cesarean section [19].…”
Section: Introductionmentioning
confidence: 99%